Elucidation of impact event recorded in the lherzolitic shergottite NWA 7397. (28th August 2021) - Yoshida, Masashi; Miyahara, Masaaki; Suga, Hiroki; Yamaguchi, Akira; Tomioka, Naotaka; Sakai, Takeshi; Ohfuji, Hiroaki; Maeda, Fumiya; Ohira, Itaru; Ohtani, Eiji; Kamada, Seiji; Ohigashi, Takuji; et al.
Abstract: The (plagioclase) lherzolitic shergottite Northwest Africa (NWA) 7397 consists of poikilitic and non‐poikilitic lithologies. Coarse‐grained low‐Ca pyroxene oikocrysts enclose olivine and chromite grains in the poikilitic lithology. The major constituents of the non‐poikilitic lithology are olivine, Ca‐pyroxene, and plagioclase. Minor amounts of chromite, ilmenite, alkali feldspar, Ca‐phosphate, and iron‐sulfide are included in the non‐poikilitic lithology. Most plagioclase grains in the non‐poikilitic lithology have become maskelynite. A melt pocket occurs in the non‐poikilitic lithology. Plagioclase in contact with the melt pocket has dissociated into zagamiite + stishovite. Apatite and merrillite entrained in the melt pocket have transformed into tuite. Olivine in contact with the melt pocket has dissociated into bridgmanite (almost vitrified) + ferroan‐periclase. Alteration products, iron oxides and hydroxides, also occur in the dissociated olivine although it is not clear when the aqueous alteration occurred. The dissociation reactions of olivine and plagioclase into the high‐pressure polymorphs (bridgmanite, ferroan‐periclase, zagamiite, and stishovite) are found from lherzolitic shergottites for the first time. The estimated peak shock‐pressure and ‐temperature conditions recorded in melt pockets of NWA 7397 are ˜23 GPa and 2, 000 °C at least, respectively, based on the high‐pressure mineral assemblages.